Impact of Education on Economic Development - Lakshman Chandra Pal (UIN Sunan Gunung Djati Bandung, 2023)
Education is widely acknowledged as the most important tool for socioeconomic development in a country. It catalyzes boosting productivity and promoting technological advancements. There is a clear positive relationship between education levels and stages of economic growth. As the population's education level improves, it opens up and expands various sectors of the economy, including secondary, tertiary, and quaternary sectors, leading to increased job opportunities and contributing to the overall size of the country's gross domestic product. Qualitative research methods were employed in this study to uncover the impact of education on economic development, with a specific focus on the agriculture, manufacturing, and earnings sectors. The study explored the intricate connections between education and these sectors through document analysis, and observations. The findings highlighted the transformative power of education in driving sustainable and inclusive economic progress. Education also plays a pivotal role in uplifting agricultural and industrial productivity by adopting modern inputs and technology, resulting in higher wages for the workforce. Educated individuals tend to earn more, invest in their family's well-being and healthcare, and enjoy longer lives, thereby fostering societal development. This paper contributes to the existing body of knowledge by comprehensively understanding how education influences economic development, particularly in the agriculture, manufacturing, and earnings sectors. It underscores the importance of education as a driver of sustainable and inclusive growth, emphasizing the need for continued investment in education to ensure long-term socioeconomic progress.